Triple a syndrome in Japan. Issue 3 (17th July 2013) - Ikeda, Masanori; Hirano, Makito; Shinoda, Keiich; Katsumata, Noriyuki; Furutama, Daisuke; Nakamura, Katsuya; Ikeda, Shu‐Ichi; Tanaka, Toshifumi; Hanafusa, Toshiaki; Kitajima, Hiroyuki; Kohno, Hitoshi; Nakagawa, Mizuho; et al.
ABSTRACT Introduction Triple A syndrome is an autosomal recessive disease, characterized by esophageal achalasia, alacrima, and adrenal insufficiency, as well as involvement of the central, peripheral, and autonomic nervous systems. This disease mimics amyotrophic lateral sclerosis in some patients. The causative gene encodes ALADIN, a nuclear pore complex (NPC) component. Only 5 patients have been reported in Japan. Methods We conducted the first nationwide survey of triple A syndrome. Identified mutants were expressed as GFP‐fusion proteins in cultured cells. Results Two new patients were identified, and 1 had a novel mutation (p.Ser182fsX19). All mutant proteins tested were mislocalized from NPC to cytoplasm. Conclusions The most consistent neurological manifestation of triple A syndrome in Japanese patients was progressive bulbospinal muscular atrophy with both upper and lower motor neuron involvement, which mimicked motor neuron disease, similar to that seen in patients in Western countries. The identification of the new patients suggests that more cases are undiagnosed in Japan. Muscle Nerve48: 381–386, 2013